USING NEURAL NETWORKS IN THE PROCESS OF IMAGE COMPRESSION - Могильний, О.А.; Бреус, Б.В. (Modern engineering and innovative technologies, 2023)
The main attribute of neural networks is determining relationships among different parameters of information, which allows providing it more densely through the detection and rejection of unnecessary information (lossless compression) or through rejectio